Defining "Girls" and "Girl Children" in Social and Legal Terms - Laura Guercio (Research Aspects in Arts and Social Studies Vol. 8, 2023)
The purpose of this chapter is to investigate whether a clearer lexical and conceptual distinction between the various stages of development, from birth to adulthood, is needed to better recognize and protect the needs of the young female population affected by armed con?ict. Should girls and girl children fall into the same age category? Can the generic macro category of children, provided by international law starting with the Convention on the Rights of the Child, be considered adequate to satisfy the needs of social and legal protection of the different phases of development towards adulthood? These questions can raise serious sociological and juridical complications. As a result, without a clear definition in place, also the category of girl children risks being confused with the category of girls, and might not be noticed for its specific characteristics and needs. This analysis proposes a reflection on the use of a more precise definition and conceptualization of the terms girls and girl children, as two distinct age stages with distinct physical and psychological development, based on intersectional feminist theory.